Relevance of distance learning in wartime conditions - Protsak , T.V.; Proniaev , D.V.; Zabrodska , O.S. (Морфологія / Morphologia / Morfologìâ, 2023)
Relevance. The beginning of martial law on the territory of Ukraine on February 24, 2022, accompanied by a full-scale armed aggression, posed great challenges to the education system. The transition to distance learning made it possible to resume the educational process and complete the 2022-2023 academic year in difficult conditions of martial law. An analysis of the world experience in implementing distance learning using Internet technologies shows that it has many advantages over traditional methods, such as constant access to educational materials, choosing one’s own pace of learning, cost-effectiveness, etc. The combination of conventional and distance learning is a more effective medical education hall. Thus, distance learning is not just a set of infrastructure for the implementation of distance learning, but a learning concept that includes various technologies and learning tools. Higher educational institutions, regardless of the chosen form of education, continue to implement the educational program chosen and approved at the beginning of the academic year. For temporarily displaced students studying in an educational program that is different from that implemented in other educational institutions, teachers are guided by distance learning, providing modern material that students have mastered before. Conclusion. So, distance learning under martial law solves many problems that education in Ukraine faces. At the same time, distance learning requires the joint efforts of parents, students and teachers to achieve the necessary learning outcomes, as well as government support. The combination of traditional and distance learning methods has shown the greatest effectiveness in medical education. Thus, the introduction of distance learning will solve the following problems: - create a flexible infrastructure to provide e-learning opportunities to all students and teachers; increase the level of digital literacy of the academic community; provide high educational standards for students and teachers. The classic synchronous learning model has many disadvantages, especially the geographic distance of individual students and teachers (e.g., different time zones) during an air raid.